Analisis Faktor-Faktor Yang Memotivasi Manajemen Perusahaan Melakukan Tax Planning (Studi Pada Perusahaan Industri Kimia Yang Terdaftar Di Disperindag Surabaya 2010) - Kadariyanty, Jofita Meida; Suhartini, Dwi; Thamrin, Tamadoy (AKRUAL: Jurnal Akuntansi, 2012)
Abstract Tax Planning is a medium to fulfill tax obligations but the amount of tax paid can be kept to a minimum to obtain the expected profit and liquidity. In 2010, the realization of tax revenues at Direktorat Jendral Pajak Jawa Timur I Surabaya was only 92% of the target set. One factor that could lead to unachieved target is the tax planning that done by some companies. The purpose of this study is to analyze the factors that motivate company management to do tax planning in chemical industry that registered in Disperindag Surabaya in 2010. Respondents are the employees that work on finance or tax department on medium and large chemical industry company that listed Disperindag in 2010 which has been implementing tax planning, with the 32 respondents. Analysis technique used is multiple linear regression analysis. The conclusion of the analysis is that the tax policy and tax law are not the motivating factor in the company's management to tax planning, while the tax administration is a factor that can motivate the management firm in doing tax planning, so the hypothesis that tax policies, tax laws, and tax administration are all factors that motivate company management in doing tax planning in a chemical industry company registered in Disperindag Surabaya 2010.